An Exploration of the Reluctant Fundamentalist from Multicultural Perspective - Rajab, Shazia; Khan, Madeha; Shehzin, Naina (Pakistan Languages and Humanities Review, 2022)
This paper interrogates multiculturalism in The Reluctant Fundamentalist by Mohsin Hamid. Multiculturalism is a technique which author use to tell their stories. When analyzing a novel, it is important to identify this technique. It is used in order to shed light on the ways in which they function in the story. Mohsin Hamid, an emerging novelist of Pakistan has given a new identity to the genre of Pakistani English Writing through his popular novels Moth Smoke and The Reluctant Fundamentalist and How to get Filthy Rich in Rising Asia. In his first two novels Moth Smoke and the Reluctant Fundamentalist, Hamid has tried two different types of narrative techniques. While he has used Multiple Narrative Technique in Moth Smoke, in The Reluctant Fundamentalist, he uses monologue. The present research proposes to explore how these narrative techniques have their validity to theme and message, the novelist conveys. This study is going to focus on multiculturalism in The Reluctant Fundamentalist. Written in a critical time, this novel contains too different social issues of Pakistan. It is believed that narrative technique has a vital role to express the temperament of the characters hence; this paper aims at studying how the narrative technique “Monologue “and “Multiple Narrative” and “Multiculturalism” do express the temperament of characters in the selected novel.